COVID-19 중의 진료지침에 수록된 예방 처방 분석 - 김상현; 신상원; 김종현; Sanghyun Kim; Sang-won Shin; Jong-hyun Kim (대한예방한의학회지, 2023)
Objectives : This study collected and analyzed information related to preventive formulas from continuously published and revised COVID-19 treatment guidelines in various regions of China. Methods : We collected treatment guidelines published in different regions of China and categorized formulas for prevention and medical observation period listed in them according to the editions. The categorized preventive formulas were compared by type and target group. Results : Herbal medicines used for prevention included formulas derived from Korean medical classics, such as Okbyeongpungsan(玉屏風散) and Eunkyosan(銀翹散). The newly composed formulas, totaling over 100, were created by adding, subtracting, and combining formulas such as Sang-gukeum(桑菊飮), Eunkyosan(銀翹散), Sasammaekmundongtang(沙參麥門冬湯), Okbyeongpungsan(玉屏風散), Gwakhyangjeong-gisan(藿香正氣散), and Soshihotang(小柴胡湯). Patent medicines including Huoxiangzhengqi capsule(藿香正氣膠囊), Lianhuaqingwen capsule(連花淸瘟膠囊), Shufengjiedu capsule(疏風解毒膠囊), and Jinhuaqinggan granule(金花淸感顆粒) were frequently used, mainly targeting close contacts. These medicines were used differently depending on the specific population group, such as the general population, the elderly, children, pregnant women, and patients with underlying diseases, and were also applied differently according to the individual's constitution. Conclusion : We were able to identify various background factors contained in the guidelines for the use of preventive formulas presented by TCM group, and understand the social conditions that enabled the group to provide such guidelines. Through this, thorough preparation should be made so that the Korean Medicine can actively respond to another future pandemic.